Mediation training and accreditation for the mediators: a commentary - Rahmat, Nur Ezan; Abdul Hak, Nora (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
Mediation training is very important to ensure that mediators are at the best position to be neutral third parties, and can effectively exercise a significant amount of authority and power over disputants. Malaysian Mediation Centre (MMC) is an institution which provides mediation training for those who are interested to become certified mediators in Malaysia. The mediation training offered by MMC is based on Australian model and in fact most of the trainers are from Australia. The Malaysian Mediation Act 2012 is silent on mediation training and practice for the mediators. Mediation training is related to the issues on qualification and accreditation of mediators since a good quality mediation training will reflect the overall practice of mediation. This paper is a summary and analysis of the literature on issues related to mediation training and practice. Some models of mediation training are also highlighted. The information and knowledge will help mediation trainers and programme administrators as they seek to ensure that the training they provide is of the highest quality possible. This study was funded by the Ministry of Higher Education (MOHE) under the Fundamental Research Grant Scheme (FRGS).